Effects of dietary iodine level on reproduction performance of gestation sow - XI Gang; XU Zi-rong; Qian Li-chun (浙江大学学报. 农业与生命科学版)
Effects of dietary iodine level on reproduction performance of gestation sow, serum parameters of sow and newborn piglets were studied. The results showed that iodine deficiency of sow could be avoided by adding 0.15 mg/kg iodine in diet. But the litter size could be increased 0.99, 0.78, 0.25 piglet per litter, average newborn piglets weight could be increased by 9.04% (P<0.05), 9.57% (P<0.05), 1.06% average litter weight could be increased by 19.27% (P<0.05), 12.75%, 6.73%, in trial group 1, 2, 3, which were fed with the diet adding 0.50, 1.00, 1.50 mg/kg iodine, respectively. The serum parameters of sow and the thyroid weight were not affected by dietary iodine level, but the T3 level of newborn piglets were increased by 21.36%, 33.98%, 49.03% (P<0.05), the liver weight were decreased by 16.53%, 10.38%, 17.23% (P< 0.05). The kidney weight were decreased by 4.97%, 27.76% (P<0.05) and 29.01% (P<0.05) in trial groups, respectively.